POTENTIAL OF MICRO, SMALL AND MEDIUM BUSINESS (MSME) PROCESSING INDUSTRY SECTOR EAST JAVA IN RESPONDING TO THE CHALLENGES OF GLOBALIZATION - Angginta Ramdani Ibrahim (East Java Economic Journal, 2017)
The global competition demands Indonesia to compete with other countries in international market. East Java is a province which gives big contribution to Indonesia’s GDP. From year to year, the source of economic growth in East Java is still dominated by the processing industry especially by the Small and Medium-Sized Enterprises (SMEs) sector. This sector is able to contribute more than 50% to East Java’s gross domestic product (GDP). Considering that, the sectoral development could be more effective to deploy in this sector for it is the prime mover of East Java’s economy. In addition to the contribution to GDP, this sector is also able to solve the employment issues and the demand fulfillment. To collect the datas, writer used questionnaire to gain the primary data with the East Java SMEs players as the respondents. Then the data was processed using Balance Scorecard approach to measure SMEs’ performance. Besides that, writer also used the secondary data that obtained by the literature study method. In result, it shows that SMEs has a promising prospect in facing external and internal challenges and pressures. Thus, this result indicates that SMEs could promote the East Java’s economy and could be a solution for Indonesia to face the global competition, especially the ASEAN Economic Community (AEC) that will be officially enacted in the end of 2015.